Analysis of the Tensile Strength of Composite Material from Fiber Bags - Ery Diniardi; Nelfiyanti Nelfiyanti; Kisman H Mahmud; Hasan Basri; A I Ramadhan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2019)
The use of composite materials in Indonesia, as a nonmetal alternative material has begun to increase. Composite use has grown from water tanks from fiberglass materials, household appliances, children's toys, sports equipment, furniture/interior design to automotive components and aircraft. Many of the advantages of this composite material include hand, strong, anti-corrosion, finely tuned finish. Its mild nature has a direct impact on energy savings. The prospect of composite materials as a non-metal alternative material is rapidly growing and its use. Various types of reinforce used can be influenced by the prices available, so seek alternatives as a commonly used glass fiber substitute woven rowing. The substitute used is a sack of gourds of the same kind as woven rowing, from which the same type of fiber is tried to find its strength by undergoing a pull test. And as a result of the test the mateial can know its power.